Dynamics of waterborne contaminations of agricultiral purposes by salt of high-density metal in the conditions of poltava region - Коваль, В. В.; Наталочка, В. О.; Ткаченко, С. К.; Міненко, О. В. (Scientific Progress & Innovations, 2012)
Laboratory studies undertaken between 2002 and 2008 by Poltava Regional state design and technology centre for protection of soil fertility and foodstuff quality concluded that surface and ground waters of the Poltava Region are not contaminated by heavy metals salts. Therefore, these conditions allow our region to develop agro-ecological business and become a leader in the production of high quality foodstuffs and in particular ecologically clean products. However, one of the preconditions of this process is the availability of unbiased data on the agroecological state of ground and surface water resources and methods of land use in the current environmental conditions, which remain reasonably stable. The results of the studies undertaken in recent years show that environmental conditions in Poltava Region are among the most favourable in Ukraine.